PENJATUHAN PIDANA MATI DI INDONESIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Anjari, Warih (E-Journal Widya Yustisia, 2018)
Criminal punishment is the most important part of the criminal justice process . Application of capital punishment by the state through the state court decision means taking the right convict life . The right to life is a human right that is non derogable . Therefore, its application should pay attention to the Human Rights convicted . The objective of this paper is to know: (1). whether the imposition of the death penalty for offenders is contrary to the Human Rights (2). The criteria for the imposition of the death penalty for crimes that do not conflict with the Human Rights. The method used is a normative juridical approach using secondary data. The conclusions that: (1) the imposition of the death penalty is contrary to human rights, but its application can be justified by reason of defending human rights, (2) only applied to crimes that are beyond the limits of humanity and the destruction of human civilization. Suggestions author implementation of the criminal justice process is transparent and fair.